Theoretical Analysis of Non-ablative Laser Texturing of Silicon Surface with a Continuous Wave Fiber Laser - Farrokhi, Hamid (2015)
Si is highly transparent to infrared fiber laser (λ=1090 nm) and the laser is not regarded as a suitable tool for ablation based silicon surface texturing. However, we have shown non-ablative texturing of Si surface is possible provided that suitable laser power and dwell time are chosen to produce peak surface temperature above the Si effective oxidation point of 1250 K and below the Si melting point of 1690 K. The phenomenon is explained through theoretical thermal analysis. The Kirchhoff transform is used to include the temperature dependent thermal conductivity. It is shown that with carefully adjusting laser parameters localized oxidation occurs and results in the formation of regularly patterned micro-bumps.